IL-12 and neutralization of endogenous IL-10 revert the in vitro antigen-specific cellular immunosuppression of paracoccidioidomycosis patients - Romano, Carla C.; Mendes-Giannini, Maria José Soares [UNESP]; Duarte, Alberto J.S.; Benard, Gil (Elsevier, 2002)
Treatment of patients with paracoccidioidomycosis is still a challenge. Patients present defective lymphoproliferation and IFN-γ responses to the main Paracoccidioides brasiliensis antigen (gp43), which correlates with disease severity. Here, we demonstrated that the patients show also a defective synthesis of interleukin (IL)-12. Therefore, we attempted to revert this immune disfunction by adding IL-12 and neutralizing anti-IL-10 antibody to gp-43-stimulated peripheral blood mononuclear cell cultures. Both treatments increased IFN-γ secretion to levels observed with healthy sensitized individuals, but affected proliferation only modestly. When combined, the treatments further increased IFN-γ synthesis and cell proliferation. The addition of suboptimal concentrations of IL-2 also further increased the IL-12-mediated secretion of IFN-γ. Interestingly, the immune modulation was mostly antigen-specific, since the responses to Candida albicans' antigen were not affected. These results suggest that appropriate immune intervention with cytokines and/or anti-cytokines may help in the treatment of PCM. © 2002 Elsevier Science Ltd. All rights reserved.
Keywords: Interleukin-10; Interleukin-12; Paracoccidioides brasiliensis; Paracoccidioidomycosis; gamma interferon; glycoprotein; glycoprotein gp 43; interleukin 10; interleukin 12; interleukin 2; neutralizing antibody; unclassified drug; 43 kDa protein, Paracoccidioides; fungal protein; fungus antigen; oligosaccharide; adolescent; adult; aged; cell proliferation; cell stimulation; clinical article; controlled study; cytokine production; cytokine release; human; immune deficiency; immune response; immunomodulation; lymphocyte proliferation; mononuclear cell; priority journal; school child; South American blastomycosis; biosynthesis; child; drug antagonism; drug effect; immunological tolerance; immunology; in vitro study; lymphocyte activation; middle aged; Paracoccidioides; serodiagnosis; Adolescent; Adult; Aged; Antigens, Fungal; Child; Glycoproteins; Human; Immune Tolerance; In Vitro; Interferon Type II; Lymphocyte Activation; Middle Age; Neutralization Tests; Oligosaccharides; Support, Non-U.S. Gov't; Fungal Proteins; Humans; Middle Aged; Candida; Candida albicans